2006
DOI: 10.1080/03655230600895226
|View full text |Cite
|
Sign up to set email alerts
|

The role of cognition in tinnitus

Abstract: There are yet relatively few published studies on cognitive functioning in tinnitus patients. Most research has been conducted by a few separate research groups. However, the available studies clearly implicate an important role of cognitive processes at different levels from basic cognitive function to more conscious appraisal of the consequences of tinnitus. Finally, a tentative model of the road from tinnitus generation to annoyance via cognitive function is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
101
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(110 citation statements)
references
References 20 publications
6
101
0
3
Order By: Relevance
“…Attentional deficits due to thalamocortical functions were reported by scalp-recorded auditory-evoked responses (P50 potential) but no correlations of sleep disturbance or tinnitus severity with reaction-time 16 have been found. It has been reported that tinnitus and cognition are inseparable 7 as neurobiological model involving (i) brain areas (nucleus accumbens/ limbic/ sympathetic); (ii) modified GABAergic, serotonergic, adrenergic and cholinergic afferents (iii) sensory perception 5,13,17 , and (iv) heterogenous multimodal processing that affects the patients' quality of life 13,18 so should be taken into account in diagnosis and rehabilitation 7,9 . Thus, objective of the present study was to find any association of auditory phantom sensation (subjective tinnitus) with cognitive performance of patients to enhance the knowledge for planning focused, targeted and cost effective management.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Attentional deficits due to thalamocortical functions were reported by scalp-recorded auditory-evoked responses (P50 potential) but no correlations of sleep disturbance or tinnitus severity with reaction-time 16 have been found. It has been reported that tinnitus and cognition are inseparable 7 as neurobiological model involving (i) brain areas (nucleus accumbens/ limbic/ sympathetic); (ii) modified GABAergic, serotonergic, adrenergic and cholinergic afferents (iii) sensory perception 5,13,17 , and (iv) heterogenous multimodal processing that affects the patients' quality of life 13,18 so should be taken into account in diagnosis and rehabilitation 7,9 . Thus, objective of the present study was to find any association of auditory phantom sensation (subjective tinnitus) with cognitive performance of patients to enhance the knowledge for planning focused, targeted and cost effective management.…”
Section: Introductionmentioning
confidence: 99%
“…It is conscious perception due to the multiple, parallel and overlapping brain networks 4 . Chronic tinnitus is maladaptive neuronal plasticity and subsequent hyperactivity in primary and secondary auditory pathways, higher-order association areas and parts of the limbic system 2,3,[5][6][7] . Tinnitus might be associated with hyperacusis, sound distortion, sleep disturbances and psychological symptoms such as affective disorders, phonophobia, and/or depression 2,5,8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several therapeutic approaches-including counseling and behavioral therapy (Andersson & McKenna, 2006;Cima, Andersson, Schmidt, & Henry, 2014;Tyler, Stouffer, & Schum, 1989;Wilson, Henry, Andersson, Hallam, & Lindberg, 1998), the provision of hearing aids (Kochkin & Tyler, 2008;Kochkin, Tyler, & Born, 2011;Searchfield, Kaur, & Martin, 2010;Shekhawat, Searchfield, & Stinear, 2013), and sound therapy devices (Hoare, Searchfield, El Refaie, & Henry, 2014;Tyler, Stocking, Secor, & Slattery, 2014)-can be effective for many people.…”
Section: Discussionmentioning
confidence: 99%
“…and consequent inappropriate behaviors (use of ear plugs, anxious or phobic reactions to ST perception) that promote the persistence of ST related discomfort (Andersson and McKenna 2006). It is for this reason that cognitive and behavioral therapies have been widely and successfully included in the multidisciplinary therapeutic management of tinnitus patients (Caffier et al 2006;Londero et al 2006).…”
Section: Subjective Tinnitus Pathophysiologymentioning
confidence: 99%